Malt barley grain market participation and level of participation by smallholder farmers in Central Ethiopia: a Heckman two-stage model approach - Dejene Mamo Workie; Workalemahu Tasew; Beneberu Teferra (Agriculture & Food Security)
Abstract Background Ethiopia has enormous potential for malt barley production. However, the local supply is insufficient to meet the demand for both the existing and emerging malt and beer factories. As a result, millions of dollars were being spent nationally to import malt. This study sought to underscore the factors influencing smallholder farmers' decision to participate in malt barley marketing and the level of participation in Central Ethiopia. A multi-stage sampling method was used to select representative sample households. Descriptive statistics and Heckman two-stage model were used to analyze the data. Results The result of the probit model revealed that malt barley producer farmers' decision to participate in the malt barley grain market was determined by age and formal education level, malt barley farming experience, amount of malt barley grain produced, total livestock holding, distance from local cooperative and nearest market and household access to enough stable food; whereas, the ordinary least squares regression results indicated that malt barley producer farmers' level of participation in the malt barley grain market was determined by the formal education level of the household head, total livestock holding, and distance from the local cooperative. Conclusions The policy recommendation of the study were raising farmers' awareness of malt barley quality parameters, organize producer farmers in nearby agricultural cooperatives, creating suitable transportation system, attractive grain prices, alternative stable food crops and forages species. In addition, collaborating with young and educated people will enhance malt barley output and market supply.